Preliminary taxonomic study on homestead flora of four districts of Bangladesh: Magnoliopsida (Bangladesh Journal of Plant Taxonomy, 2020)
This study has documented the contemporary taxonomic information on the species of the class Magnoliopsida (Dicotyledons) extant in the homestead areas of Dhaka, Gazipur, Manikganj and Tangail districts of Bangladesh. In these areas, the Dicotyledons are comprised of total 455 species under 302 genera belonging to 78 families. Fabaceae with 41 species is the largest family and Solanum and Lindernia are the largest genera. Total 238 species are herbs followed by 129 species of trees and 88 species of shrubs. Total 332 species are economically useful. The composition and distribution of the species of this plant group are remarkably variable in the homestead areas of the four districts. The current status of seven threatened species viz., Abroma augusta, Andrographis paniculata, Aniseia martinicensis, Mucuna bracteata, Pterocarpus santalinus, Rauvolfia serpentina and Tournefortia roxburghii, included in the Red Data Book of Bangladesh and extant in the study area, has been evaluated and described. This study has identified some threats to the homestead flora and formulated some recommendations for the conservation of threatened and declining native plant species of the study area. The data provided by this study will serve as an important baseline to track the trend of changes in the floristic composition and diversity and sustainable development of plant genetic resources in the homesteads of the study area.Bangladesh J. Plant Taxon. 27(1): 37-65, 2020 (June)